EFFECTIVENESS OF PRENATAL YOGA ON PREGNANCY ANXIETY AND DEPRESSION: A SYSTEMATIC REVIEW - Astuti, Ismi Puji; Hadisaputro, Suharyo (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Physiological and psychological changes during pregnancy process can cause discomfort to pregnant women. During pregnancy, pregnant women from developed and developing countries tend to have an increase in anxiety and symptoms of depression. If not properly managed, those situations can adversely affect maternal and infant health. This systematic review is to explore the effectiveness of yoga in order to reduce anxiety and depression in pregnant women. Methods: This systematic review was based on Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA Protocol). Publication screening was carried out by filtering the 2009-2019 English and Indonesian articles from electronic data sources, namely PubMed, PsycINFO, Google Scholar and Science Direct. The keywords used in the literature searching were ?anxiety?, ?depression in pregnancy?, ?prenatal yoga?, ?yoga in pregnancy?, ?pregnancy?, and ?complementary and alternative medicine in pregnancy?. Results: The search identified 368 record, of which 8 articles were included in this study. Studies regarding to the effect of yoga in pregnant women has been shown to reduce anxiety scores, pregnancy depression, anger, sleep disorders, lower maternal cortisol hormones, improve maternal immunity and neonatal outcomes. Conclusion: Yoga could be applied as a complementary therapy that was easy, low cost, and useful for reducing anxiety and depression in pregnant women.